Plasma nitrite/nitrate and erythropoietin levels in cross-country skiers during altitude training - Schena, F.; Cuzzolin, L.; Rossi, L.; Pasetto, M.; Benoni, G. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: The aim of this study was to evaluate the effects of training at altitude on plasma nitrite/nitrate and erythropoietin levels since previously it has been reported an interaction of the NO/cGMP system in erythropoietin production. METHODS: Nine physically trained cross-country male skiers, usually living at 800-1200 m altitude, underwent 6 days of intensive training at a moderate altitude of 3100 m preceeded by 2 days of acclimatisation. Six team-managers, selected as controls, did not undergo any regular physical activity in the last 5 years and during the altitude period. Haematological parameters, erythropoietin and nitrite/nitrate were measured prior to reach the place at altitude, at the end of the period at moderate altitude and 7 days after returning at home. RESULTS: Haematocrit significantly increased in controls after 8 days at altitude. Erythropoietin levels significantly increased after the intensive altitude training only in trained subjects (13.1+/-1.7 vs 6.7+/-1.7 mU x ml-1, p<0.001). Nitrite/nitrate baseline values were significantly higher in trained subjects compared to untrained (49.9+/-17.9 vs 25.4+/-2.8 &mgr;mol x l-1, p<0.01); the altitude period significantly increased nitrite/nitrate levels, in untrained subjects, to the same values observed in trained subjects under control conditions (47.0+/-10.3 &mgr;mol x l-1). CONCLUSIONS: In our experimental conditions we demonstrated the influence of hypoxia on Epo levels in athletes sustaining a short-term training and the role of a regular physical activity (partly independent from altitude hypoxia) on NO production.